Falenciak J., Gintowt E., Warkałło W., Wiliński A., Wyszyński M., Prawo rzymskie (skrypt) zeszyt 1–3 - Kupiszewski, Henryk (Czasopismo Prawno-Historyczne, 1960)
Recenzja: J. Falenciak, E. Gintowt, W. Warkałło, A. Wiliński, M. Wyszyński, Prawo rzymskie (skrypt), z. 1—3, Warszawa 1958